New taxa and phylogenetic placement of Asterinales from Brazil - Firmino, André Luiz (2013)
Infected living leaves of different host plants showing black colonies belonging to Asterinales were collected in areas of Atlantic forest of Brazil in field trips during 2009–2012. The field trips were conducted in four Brazilian states and six areas: Minas Gerais (Mata do Paraíso, Mata do Seu Nico, Mata da Biologia and near Nova Lima), Espírito Santo (Reserva Natural da Vale do Rio Doce), Bahia (Reserva Ecológica da Michelin and Serra da Jibóia) and Rio Grande do Sul (near Bento Gonçalves). Through morphological and biometric data, 13 probably new species, 4 first reported to Brazil and 5 new host records are described and illustrated. A combined phylogenetic analysis of the ribosomal sequences (18S and 28S rDNA) and protein-coding (TEF and RPB2) confirmed that Asterinales form a monophyletic clade well supported within the Dothideomycetes. The sister relationship of Schizothyriaceae and Mycosphaerellaceae within the Capnodiales and the non-relationship between Asterinales and Capnodiales were corroborated. A revision of the genera of the families Asterinaceae and Englerulaceae shows a small divergence in the number of genera when compared with others authors. An index of Asterinales from Brazil containing 151 species distributed in 47 botanical families, including two families: Asterinaceae and Englerulaceae is also provided.